Role of Hematological Score in Early Diagnosis of Neonatal Sepsis - Dey, Dipika; Sulltana, Razia; Ahmed, Wazir; Chowdhury, Mahmood Ahmed; Akter, Farhana; Dasgupta, Srabony (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Neonatal sepsis is one of the major causes of morbidity & mortality in the newborn, more so in the developing countries. Objective: The objective of this study was to evaluate the applicability of Haematological Scoring System (HSS) in early diagnosis of sepsis and its compatibility with C-reactive protein (CRP) and blood culture. Materials and methods: This prospective study consisted of 205 neonates admitted at neonatal intensive care unit of Chattogram Maa-shishu-o General Hospital with clinical suspicion of neonatal sepsis, from July 2017 to December 2017. The neonatal hematological parameter was measured in all cases. Blood culture and CRP estimation were also performed. Blood culture is considered as gold standard for diagnosis of sepsis. Score 3 and more was considered as positive Results: Out of 205 neonates of our study population, forty one (20%) had proven sepsis according to culture. Total leukocyte count showed high sensitivity & least specificity, immature to mature neutrophil ratio showed high sensitivity and high specificity. Platelet count showed high negative predictive value and least positive predictive value. The HSS was found to have a sensitivity of 82.9%, specificity of 79.8%, positive predictive value was 50.74% and negative predictive value was 94.92%. Considering the high sensitivity and negative predictive value, this study implies that score ³3 were more reliable as a screening tool for sepsis than any of the individual hematological parameter. Conclusion: HSS is a simple, easy and rapid adjunct for the diagnosis of clinically suspected cases of neonatal sepsis. It also provides an effective guideline to make decisions regarding judicious use of antibiotic therapy. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 45-48